Defining a case of work-related stress - Houdmont, Jonathan (2009)
This thesis concerns case definitions for work-related stress; that is, the criteria used for the identification of a person as presenting a case. It has its focus on case definitions used as the basis for measurement in two related domains in the British context: large-scale nationally representative workforce surveys and personal injury litigation. Together, these contribute to informing policy and practice on tackling the challenge to occupational health presented by work-related stress.